THE APPARATUS FOR ALIGNMENT OF THE PHOTOMETRIC LAMP FILAMENT - V. A. Dlugunovich; V. A. Zhdanovskii; A. A. Liplianin; S. V. Nikanenka; O. V. Tarasova (Приборы и методы измерений)
During photometric measurements involving the use of photometric lamps it is necessary that the filament of lamp takes a strictly predetermined position with respect to the photodetector and the optical axis of the photometric setup. The errors in positioning of alignment filament with respect to the optical axis of the measuring system lead to increase the uncertainty of measurement of the photometric characteristics of the light sources. A typical method for alignment of filament of photometric lamps is based on the use a diopter tubes (telescopes). Using this method, the mounting of filament to the required position is carried out by successive approximations, which requires special concentration and a lot of time. The aim of this work is to develop an apparatus for alignment which allows simultaneous alignment of the filament of lamps in two mutually perpendicular planes. The method and apparatus for alignment of the photometric lamp filament during measurements of the photometric characteristics of light sources based on two digital video cameras is described in this paper. The apparatus allows to simultaneously displaying the image of lamps filament on the computer screen in two mutually perpendicular planes. The apparatus eliminates a large number of functional units requiring elementwise alignment and reduces the time required to carry out the alignment. The apparatus also provides the imaging of lamps filament with opaque coated on the bulb. The apparatus is used at the National standard of light intensity and illuminance units of the Republic of Belarus.